A Comparative Financial Ratio Analysis Between Conventional and Islamic Banks in GCC - Banerjee, Arindam (International Journal of Accounting and Financial Reporting, 2021)
Banking framework establishes the central mainstay of any economy. Banks functions as monetary conduits between sectors that have abundance reserves and those that are in deficiency. The historical backdrop of banking in the Gulf Cooperation Council (GCC) traces all the way back to 1918 with the foundation of the primary bank in Bahrain. The territorial financial evolution is attributable to oil abundance and loaning business that spotlights on building, land and client advances. Throughout the long term, the financial framework worldwide has advanced in its contributions to suit the changing customer requests. One of the essential determinants of this change came about because of the strict convictions of individuals bringing about the remarkable development of Islamic Banking System. The prevalence of these banks are in nations with critical Muslim populace like Iran, Pakistan and Sudan but not limited to them. Islamic banks work under Sharia standards of hazard sharing and premium preclusion as appeared differently in relation to customary banks that purchase cash-flow to pool assets and offer cash-flow to produce revenue pay or benefit. This paper applies banks' endogenic elements identified with their monetary record and pay explanation and utilizing an aggregate of 24 financial ratios relating to the banks’ performance and seeks to thoroughly analyze the same among customary and Islamic banks. This examination clarifies the design, activity and the board of traditional banks in the GCC combined with the working of Islamic banks. The paper likewise intends to decide the beneficial and proficient banks among the chosen sample. The study incorporates 20 institutions, similarly dispersed among Islamic and customary banks utilizing information between the time of 2014 - 2017. The example is comprehensively ordered dependent on benefit ratios, proficiency ratios, asset indicator ratios and risk ratios. Further sub categorization is done to show up at an aggregate of 24 ratios. An independent T-test is used to determine a substantial ratio between Islamic and conventional banks.